Soft polymer membrane micro-sensor arrays inspired by the mechanosensory lateral line on the blind cavefish. (January 2015) - Kottapalli, Ajay Giri Prakash; Asadnia, Mohsen; Miao, Jianmin; Triantafyllou, Michael
This article reports the development of flexible arrays of soft membrane microelectromechanical system pressure sensors that are inspired by the functional implications of the lateral line organ present in the blind cavefish. Being blind, this fish relies on the lateral line of pressure gradient sensors present on its body to sense the surrounding obstacles. A flexible, low-powered, lightweight, sensitive yet robust microelectromechanical system sensor array is fabricated using liquid crystal polymer material. Such arrays can guide an autonomous underwater vehicle to navigate in unsteady and dirty-water environments. The object detection abilities of the blind cave characin fish are investigated through proof-of-concept experiments conducted on the live fish. Similarly, the abilities of the microelectromechanical system array in determining the velocity and distance of an underwater object are investigated by testing them in water tunnel. Experimental results demonstrate the array's ability to detect the velocity of moving underwater objects with a high accuracy and an average error of only 2.5%.